2019
DOI: 10.1016/j.iccn.2019.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of nursing rounds in the Intensive Care Unit on workplace learning

Abstract: Objectives: To evaluate the implementation of a regular Nursing Round as an educational strategy for workplace learning in an intensive care unit with a single room environment. Research Design: A multiple methods design was used. Fifty-four Nursing Rounds were observed, and nurses (n=40) completed bespoke evaluative surveys. Structured observational data and open-ended survey responses were submitted to content analysis and descriptive statistics were used to analyse survey findings. Results: Nursing Rounds i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 31 publications
0
13
0
5
Order By: Relevance
“…Team-based learning in the workplace was particularly effective in facilitating workplace transformation (Augustsson et al 2013;Eddy et al, 2016;Williams et al 2015;Tobiano et al 2019). Augustsson et al (2013) found that workplace study circles improved perceptions of palliative care, and led to a greater understanding of co-workers' ways of working.…”
Section: Preference For Workplace Learningmentioning
confidence: 99%
“…Team-based learning in the workplace was particularly effective in facilitating workplace transformation (Augustsson et al 2013;Eddy et al, 2016;Williams et al 2015;Tobiano et al 2019). Augustsson et al (2013) found that workplace study circles improved perceptions of palliative care, and led to a greater understanding of co-workers' ways of working.…”
Section: Preference For Workplace Learningmentioning
confidence: 99%
“…The research that contributed to this study was mostly a qualitative study and a quasy-experiment. Research from the reviewed studies was conducted in seven different countries, Australia (Flowers et al, 2016;Tobiano et al, 2019;East et al, 2020), United States (Blakley, Kroth and Gregson, 2011;Daniels, 2016;), Iran (Negarandeh, Hooshmand Bahabadi, and Aliheydari Mamaghani, 2014), Republic of Korea (Shin and Park, 2018), Saudi Arabia (Saleh et al, 2011), United Kingdom (Kirk and Kane, 2016), and Jordan (Ayaad et al al., 2019). Nursing rounds in the journals article used in this reviewed are implemented in a treatment room or ward that have patients with different diagnoses and some are implemented in special care environments such as medical surgery units, emergency departments, oncology units, intensive care units (ICU), elderly care unit and maternity.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Establishment of cooperation between health teams Based on a statement in the journal entitled Effectiveness of nursing rounds in the Intensive Care Unit on workplace learning that the nursing round is considered to positively influence evidence-based application in practice, identify areas for practice improvement, and the ability to communicate clinical information. Nursing Rounds allow evidence-based learning that enhances interdisciplinary collaboration (Tobiano et al, 2019) and the journal The Impact of Nurse Rounding on Patient Satisfaction in a Medical-Surgical Hospital Unit explains that the round application program also facilitates communication between members of the patient care team, encouraging teamwork which is essential for quality health care (Blakley, Kroth and Gregson, 2011). 5.Nurses able to do the nursing care model appropriately and correctly Based on a statement in the journal entitled Impact of Regular Nursing Rounds on Patient Satisfaction with Nursing Care, the nursing round is one of the methods in primary nursing management that improve the quality of nursing services.…”
Section: Raise Up a Professional Nursing Communitymentioning
confidence: 99%
See 1 more Smart Citation
“…At the micro‐level more frequent, timely, accurate and problem‐solving face‐to‐face communication between units may be required. For instance, translational simulation (Brazil, Purdy, Alexander, & Matulich, 2019) and nursing rounds (Tobiano et al, 2019) have been shown to enhance comradery across units (Rosenbaum, 2019). Promoting more opportunities for secondment in other units could also enhance relationships (Dryden & Rice, 2008).…”
Section: Relevance To Clinical Practicementioning
confidence: 99%